Family History of Diabetes: An Important Risk Factor for Developing PCOS - Sana Fayyaz, Muhammad Bilal Butt, Saima Khan, Adnan Ali, Hafiza Yasmeen Abbas, Sunita (Pakistan Journal of Medical & Health Sciences, 2022)
Background and Aim: Polycystic ovary syndrome (PCOS) is a new rising disorder of reproductive, metabolic, and endocrine disorders of young females of reproductive age suffering from insulin resistance, increased levels of androgens, and altered morphology of ovaries with multiple cysts, and oligoanovulation. The burden of disease is significantly high with a global prevalence of 5% - 10% of reproducing females. Literature has reported a positive correlation between diabetes mellitus in the family and the resultant risk of developing PCOS among the female population. This study will aim to assess the correlation between the familial history of diabetes mellitus and concurrent risk of developing PCOS in a tertiary care hospital in Lahore, Pakistan. Methodology: A cross sectional study was conducted in the Medicine and Gynecology department of Sir Ganga Ram Hospital, Lahore for duration of four months from October 2021 to January 2022. Participants were recruited following inclusion and exclusion criteria. Sample population was estimated to be 150 females. Participants were recruited by convenient sampling. After recruitment participants underwent physical, clinical, and serological assessment. Diagnosis of PCOS was made by following Rotterdam criteria. Data collection was done by 14 points questionnaire and history interview. Results: This study showed that all participants diagnosed with PCOS have a history of early menarche, increased level of heartbeats, a large volume of ovaries, and a lesser volume of uterus. Patients also showed increased peripheral follicles. Serologic outcomes of participants showed a generalized increase in TT levels and a generalized decrease in SHBG levels with 1.71 (1.04-2.23) nmol/L and 45.39 ± 24.44 nmol/L respectively. About 56.2% (n= 83) of the participants gave a history of the abnormal menstrual cycle and 70.3% (n= 104) of the population agreed to abnormal hair growth on the body. When assessing the history of diabetes mellitus prevalence among families of the participants, the results showed that 19% of the population (n= 28) gave a positive history of diagnosed diabetes mellitus of both mother and father, 21.1% of the participants (n= 31) suggested that their parents were never tested for diabetes mellitus before, whereas remaining 43.8% (n= 89) gave no familial history of diabetes mellitus. Conclusion: The study concludes that the most common characteristics of PCOS among the population of Pakistan is increased weight followed by abnormal hair growth, participants present with increased TT and decreased SHBG levels. Familial history of diabetes mellitus is considered a risk factor for developing PCOS.